Genome-wide mapping of nucleosomes in yeast - Rando, Oliver J. (Methods Enzymol, 2010)
The packaging of eukaryotic genomes into chromatin has wide-ranging influences on all DNA-templated processes, from DNA repair to transcriptional regulation. The repeating subunit of chromatin is the nucleosome, which comprises 147 base pairs of DNA wrapped around an octamer of proteins. Positioning of nucleosomes relative to underlying DNA is a key factor in the regulation of gene transcription by chromatin, as DNA sequences between nucleosomes are more accessible to regulatory factors than are DNA sequences within nucleosomes. Here, I describe protocols for mapping nucleosome positions across the yeast genome.